Human rights: from discourse to culture - Squella, Agustín (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2024)
This article examines the complex relationship between democracy and fundamental rights, arguing that a historical perspective on rights, which is indispensable, does not necessarily justify their existence in historicist terms. It notes that the expansion and generalisation of rights have posed challenges to defining a unified concept of fundamental rights. Furthermore, it criticises the romantic perception that democracy is sufficient to guarantee these rights, especially in a context of crisis of representation, corruption and other contemporary challenges.The article also addresses the disjuncture between democracy and capitalism, especially in its neoliberal form, arguing that this alliance has been problematic and has contributed to the erosion of social rights. It is stressed that while democracies may violate human rights, these violations are not systematic and there are mechanisms to denounce and correct them. The author suggests that in order to understand the current challenges in the discourse of rights, it is crucial to consider their history from Modernity to the present.
Keywords: fundamental rights; democracy; crisis of representation; history